Can a Map Be a Geographic Information Retrieval Tool? - Jan Smits (Liber Quarterly: The Journal of European Research Libraries, 2000)
This paper is intended to open up discussion on potential co-operation, which would enable participants restricted by unequal resources and technologies to participate in a pan-European project. The idea has not yet been fully developed but the purpose of the project is to allow digital maps to function not only as geographic resources and educational tools, but to act simultaneously as an interface to metadata-databases. These would contain de-scriptions of maps and spatial databases, as well as locational or geo-referenced resources in books, periodicals, and the Internet.